2015
DOI: 10.1097/opx.0000000000000649
|View full text |Cite|
|
Sign up to set email alerts
|

Relationships among Tear Film Stability, Osmolarity, and Dryness Symptoms

Abstract: Purpose To examine the relationships among tear osmolarity, tear film stability, and several measures of dry eye (DE) symptoms in a multivariable analysis. Methods A cross-sectional study was conducted with 137 subjects (68 non–contact lens [CL] wearers and 69 soft CL wearers) recruited from a university campus. Tear breakup time (TBUT) was measured noninvasively (NITBUT) and with fluorescein (FTBUT). Tear osmolarity was measured by an osmometer. Dry eye symptoms were assessed using the Dry Eye Flow Chart an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 60 publications
2
34
1
2
Order By: Relevance
“…Studies on correlation among conventional clinical tests for dry eye have been undertaken for many years [4,5,22,[44][45][46][47][49][50][51][52] with inconsistent results. Such findings confirmed the complexity of DED and how the disease is multifactorial, depending on the dry eye subtypes, symptom questionnaire used and population studied [53].…”
Section: Correlation Between T4 Metrics and Signs And Symptoms For Drmentioning
confidence: 99%
“…Studies on correlation among conventional clinical tests for dry eye have been undertaken for many years [4,5,22,[44][45][46][47][49][50][51][52] with inconsistent results. Such findings confirmed the complexity of DED and how the disease is multifactorial, depending on the dry eye subtypes, symptom questionnaire used and population studied [53].…”
Section: Correlation Between T4 Metrics and Signs And Symptoms For Drmentioning
confidence: 99%
“…62,63 Studies have shown that Asians have less stable tear films compared with non-Asians. 64,65 Despite similar lipid film thicknesses, healthy Asian subjects have a 11% to 24% shorter tear film breakup time than non-Asians. 64,66,67 Although no single component can be attributed to contact lens discomfort, a rapid tear breakup time was found to be the most consistent finding.…”
Section: Tear Filmmentioning
confidence: 99%
“…64,65 Despite similar lipid film thicknesses, healthy Asian subjects have a 11% to 24% shorter tear film breakup time than non-Asians. 64,66,67 Although no single component can be attributed to contact lens discomfort, a rapid tear breakup time was found to be the most consistent finding. 7 This suggests that even healthy Asian subjects may experience more discomfort with contact lens wear than non-Asians.…”
Section: Tear Filmmentioning
confidence: 99%
See 2 more Smart Citations